ISOLATION AND ENZYMATIC FRAGMENTATION OF GENOMIC DNA FROM UNCULTURED MICROBIAL SYMBIONTS OF Theonella sp. SPONGE AS PREREQUISITE FOR METAGENOMIC LIBRARY CONSTRUCTION - Agustinus Robert Uria; lfah Munifah; Ekowati Chasanah (Indonesian Fisheries Research Journal, 2007)
Microbial symbionts of sponges are well known as the sources of numerous bioactive products which are of potential industrial and pharmaceutical importance, including secondary metabolites, enzymes, lipids and heteropolysaccharides.